Pengaruh budaya organisasi, komitmen organisasi dan kepuasan kerja terhadap kinerja(studi kasus di PT. Cahaya Internusa Group Indonesia) - Jufnidar Jufnidar; Syamsul Ma'arif (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2018)
The purpose of this study is to determine the influence of Organizational Culture, Organizational Commitment and Job Satisfaction Against Employee Kinrja in PT. Cahaya Internusa Group Indonesia. This research uses survey method by using primary data obtained from questionnaire. The population in this study are the employees who are in the Environment PT. Cahaya Internusa Group Indonesia. The number of samples taken in this study are 148 employees who are in PT. Cahaya Internusa Group Indonesia. Samples were taken by Random Sampling technique. Testing data quality using validity test and reliability test. Data were analyzed using The Structural Equation Modeling (SEM) of the AMOS 4.0 statistical software package in the model and hypothesis assessment. The structural equation model, Structural Equation Model (SEM). The results showed that: (1) Organizational Culture positively affect Job Satisfaction. (2) Organizational Commitment has a positive effect on Job Satisfaction. (3) Job Satisfaction has a positive effect on Employee Performance (4) Organizational Culture has a positive effect on Employee Performance. (5) Organizational Commitment has a positive effect on Employee Performance. Keywords: Organizational Culture, Organizational Commitment Job Satisfaction and Employee Performance